Dysregulation of junctional adhesion molecule‐A contributes to ethanol‐induced barrier disruption in intestinal epithelial cell monolayers. Issue 23 (6th December 2017) - Chopyk, Daniel M.; Kumar, Pradeep; Raeman, Reben; Liu, Yunshan; Smith, Tekla; Anania, Frank A.
Abstract: Alcohol consumption promotes loss of intestinal barrier function. However, mechanisms by which ethanol affects the tight junction (TJ), the cellular structure responsible for maintaining the gut epithelial barrier, are not well understood. Three classes of transmembrane proteins comprise TJs: occludin, claudins, and junctional adhesion molecules (JAMs). It has recently been postulated that JAM‐A (F11R), the most abundant JAM expressed in intestinal epithelium, regulates "leak" pathway flux, a paracellular route for the nonselective permeation of large solutes. Since transluminal flux of many gut‐derived antigens occurs through this pathway, we investigated the role of JAM‐A in ethanol‐induced disruption of the intestinal epithelial barrier. Using Caco‐2 and SK‐CO15 monolayers, we found that ethanol induced a dose‐ and time‐dependent decrease in JAM‐A protein expression to about 70% of baseline levels. Alcohol also reduced Ras‐related protein 2 (Rap2) activity, and enhanced myosin light chain kinase (MLCK) activity, changes consistent with impaired JAM‐A signaling. Stable overexpression and shRNA‐mediated knockdown of JAM‐A were employed to investigate the role of JAM‐A in paracellular‐mediated flux following alcohol exposure. The paracellular flux of 40‐kDa fluorescein isothiocynate (FITC)‐dextran following ethanol treatment was decreased by the overexpression of JAM‐A; conversely, flux was enhanced by JAM‐A knockdown. Thus, we conclude that ethanol‐mediated control of JAM‐A expression and function contributes to mechanisms by which this chemical induces intestinal epithelial leakiness. Abstract : In this study, we present new evidence suggesting that dysregulation of the tight junction protein JAM‐A may contribute to the mechanisms by which ethanol disrupts intestinal epithelial barrier integrity and function. Ethanol exposure was found to reduce JAM‐A protein expression in Caco‐2 monolayers, as well as result in impaired signaling activity of JAM‐A signaling molecules Rap2 and MLCK.